Impaired episodic-like memory in a mouse model of Alzheimer's disease is associated with hyperactivity in prefrontal-hippocampal regions - Tan, Sijie (2023)
Alzheimer's disease (AD) is a degenerative brain disorder with a long prodromal period. An APPNL-G-F knock-in mouse model is a preclinical model to study incipient pathologies during the early stages of AD. Despite behavioral tests revealing broad cognitive deficits in APPNL-G-F mice, detecting these impairments at the early disease phase has been challenging. In a cognitively demanding task that assessed episodic-like memory, 3-month-old wild-type mice could incidentally form and retrieve 'what-where-when' episodic associations of their past encounters. However, 3-month-old APPNL-G-F mice, corresponding to an early disease stage without prominent amyloid plaque pathology, displayed impairment in recalling 'what-where' information of past episodes. Episodic-like memory is also sensitive to the effect of age. Eight-month-old wild-type mice failed to retrieve conjunctive 'what-where-when' memories. This deficit was also observed in 8-month-old APPNL-G-F mice. c-Fos expression revealed that impaired memory retrieval in APPNL-G-F mice was accompanied by abnormal neuronal hyperactivity in the medial prefrontal cortex and CA1 dorsal hippocampus. These observations can be used for risk stratification during preclinical AD to detect and delay the progression into dementia.